Pengaruh Corporate Governance Terhadap Internal Control Disclosure Perusahaan Manufaktur Terdaftar Di BEI - Fanny, Ardiansyah (Jurnal Paradigma Akuntansi, 2021)
The objective of this research is to obtain empirical evidence about the effect of corporate governance  toward internal control disclosure of manufacture company that listed on Indonesia Stock Exchange for the period 2016-2018.  Sample was selected by purposive sampling method resulted on 115 companies which published completed information that required for this research. Data processed using Statistical Package for the Social Sciences (SPSS) ver 23.0 program. The results of this research show that managerial ownership has negative and significant effect while institutional ownership has negative and not significant effect toward internal control disclosure. Size of commissioner and number of independent commissioner has positive and significant effect while audit committee education has positive and no significant effect toward internal control disclosure.